Chitosan-graft-poly(n-butyl acrylate) copolymer: Synthesis and characterization of a natural/synthetic hybrid material. (10th July 2016) - Anbinder, Pablo; Macchi, Carlos; Amalvy, Javier; Somoza, Alberto
Highlights: Graft copolymerization was employed to obtain a natural/synthetic hybrid material. Well defined core–shell morphology was obtained. Chitosan films swelling is reduced without a decrease of the surface hydrophilicity. Free nanohole volumes and their fractions were modified by grafting. Chitosan-pBuA systems show a great potential as biodegradable packaging materials. Abstract: Two chitosan polymers with different deacetylation degree and molecular weight were subjected to grafting reactions with the aim to enhance the properties of these bio-based materials. Specifically, n -butyl acrylate in different proportions was grafted onto two different deacetylation degree (DD%) chitosan using radical initiation in a surfactant free emulsion system. Infrared spectroscopy was used to confirm grafting and products grafting percentage and efficiency were evaluated against acrylate/chitosan ratio and DD%. Thermal and structural properties and the behavior against water of the raw and grafted biopolymers were studied using several experimental techniques: differential scanning calorimetry, transmission electron microscopy, dynamic light scattering, water swelling, contact angle and positron annihilation lifetime spectroscopy. The influence of the grafting process on the morphological and physicochemical properties of the prepared natural/synthetic hybrid materials is discussed.